If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(v + -72) = 72 Reorder the terms: 6(-72 + v) = 72 (-72 * 6 + v * 6) = 72 (-432 + 6v) = 72 Solving -432 + 6v = 72 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '432' to each side of the equation. -432 + 432 + 6v = 72 + 432 Combine like terms: -432 + 432 = 0 0 + 6v = 72 + 432 6v = 72 + 432 Combine like terms: 72 + 432 = 504 6v = 504 Divide each side by '6'. v = 84 Simplifying v = 84
| 16x+x^2=45 | | f(x)=14-1/2x^-3 | | 2/5-4(1/2-5/8) | | -2m/16= | | 16/51(3/10) | | 0=-12x^2-9x+1 | | W/3-3=1 | | 14=7/8x | | 7/-4= | | .5+.4s=s-.75 | | 2/5*4/35 | | (U+7)(U-5)= | | 10-2g=8 | | .5-.4s=s-.75 | | xy+3y=-9 | | -7x-2(5x)=-13 | | 3/5(6/13) | | 21+x=546 | | 5n-(100+2n)=4n-2(10+n) | | x+3=5x+1 | | 4e(5x)=20 | | 10s^3-22s^2+4s= | | 1/8(1/5) | | 6(x+6)-8x=30 | | 21n^2+7n+14=11 | | 14+x=24 | | 3x^2-7x=120 | | 4/9(17) | | 10s^3-22s^2+4s=2s | | .5cos(.25x)=0 | | 9+x=522 | | (9-2)/(5-9)= |